AB0762 Saving money and reducing infliximab waste using weight based chart for standardised doses. (23rd January 2014) - Yousif, A.; Williamson, L.; Muether, M.; Collins, D.; Price, E.
Abstract : Background: Infliximab is a TNF inhibitor widely used for the treatment of inflammatory arthritis (rheumatoid, psoriatic, and ankylosing spondylitis), inflammatory bowel disease, skin psoriasis and other immunological conditions. The recommended dose ranges between 3-5 mg/kg administered at 6-8weeks interval and it is produced in 100mg vials at a cost of £450 each (UK). Literature review points to a minimally effective dose of 3mg/kg and maximum treatment interval of 8 weeks. In general it is more cost effective to decrease the time interval between treatments than increase dose. In order to minimise wastage we adopted a policy of vial sharing between patients which for logistical reasons did not work well. In May 2012 vial sharing was abolished by our hospital pharmacy because of concerns about possible infection risk. This prompted us to re-examine our Infliximab dosing regime, with the aim of minimising waste. Objectives: To assess the potential cost saving of a simple, innovative method for calculating infliximab dose using a weight based chart for standardised doses, based around 3mg/kg, rounding doses up or down to the closest multiplier of 100. Methods: We calculated the theoretical maximum drug cost based on 3 mg/kg for RA and PsA, 5 mg/kg for and AS, using our patients on infliximab through 2011 as a reference point. We reviewed drug charts and calculated the actual use over the same time period. We recalculated what both would have been if the new regimen had been adopted. Results: The total number of patients treated was 26 (18 RA, 2 PsA, 3 AS, 3 Bechets). Patients mean age was 54 and mean weight of 83.88 kg (range 58-140Kg). This gave a theoretical maximum cost of £188550 annually. Actual costs in 2011 due to dosing variations and failed attendances was £162000. The theoretical maximum cost using our new method would have been £147150 for the same group of patients, with a mean dose calculated by weight of 2.98 mg/kg (range: 2.50-3.45mg/kg). Using our new method would have saved between approximately £ 41, 100 (22%) annually as maximum, and £ 14, 850 (9%) based on actual use. Weight chart: Conclusions: We present a simple method of Infliximab dosing based around a mean dose of 3 mg/kg with anticipated cost savings of between £14850 - £41100 (9% - 22%) per year. This regime also avoids the waste of discarding part-used vials. Some of this saving might be offset by the need to increase the frequency of infusions. Individual patients care is being carefully reviewed to ensure no loss of efficacy or significant personal inconvenience due to change in practice, with none identified to date. References: Somerville M, Brooksby A, Scott D G I. Maximizing the use of scarce resources: vial optimization. Letter to the auditor. Rheumatology 2006;45:353–354 Bemt B, Broeder A, Snijders G et al. Sustained effect after lowering high dose infliximab in patients with rheumatoid arthritis: a prospective dose titration study. Ann Rheum Dis. doi:10.1136/ard.2007.083683 Pavelka K, Jarosova K, Suchy D et al. Increasing the infliximab dose in rheumatoid arthritis patients: a randomised, double blind study failed to confirm its efficacy: : a randomized, controlled trial. Ann Rheum Dis. 2009 Aug;68(8):1285-9 Disclosure of Interest: None Declared